An Analytical Model for Three-Tower Self-Anchored Suspension Bridges with Longitudinal Tower-Girder Connections. (February 2023) - Liu, Shuang; Chen, Zhijun; Cao, Hongyou; Shao, Changyu
Abstract: This study proposes an analytical model for three-tower self-anchored suspension bridges with different longitudinal tower-girder connections based on the deflection theory. The proposed model utilizes horizontal springs to model the stiffness of the tower-girder connections and includes the nonlinear effect caused by the stiffness of the towers and the tower-girder connections. The comparison analysis demonstrates that the structural responses predicted by the proposed analytical model agreed well with those gained by the nonlinear finite element method under various live load cases. A parametric analysis is carried out to examine the effects of different parameters, including the side-to-main span ratio, stiffness of the towers, sag-to-span ratio, axial and flexural stiffness of the girder, on the mechanical characteristics of three-tower self-anchored suspension bridges. The results show that decreasing the side-to-main span ratio and the sag-to-span ratio have the same effect as increasing the flexural stiffness of the girder on improving the static behavior of three-tower self-anchored suspension bridges. The tower-girder longitudinal connection has an apparent impact on the structural performances of the bridges, and the structural system with a tower-girder connection at the mid-tower always has the smallest structural responses under live loads.